Factors influencing the selection of umrah travel agencies in Malaysia / Sharifah La'aiba Syed Redhwan - Syed Redhwan, Sharifah La'aiba (Faculty of Business Management, 2017)
Religious travel has grown consistently with the growth of the tourism industry worldwide (Siti Hasnah Hassan, 2015). In selecting an agent is a vital part of Umrah preparation. It is important that pilgrims understand the criteria and apply them when buying an Umrah package. However, many cases like fraud and scam occurred in Malaysia where the agents hide some information from the pilgrims which lead to the problem and poor satisfaction level towards the agent. Besides, visa issues where the agent did not handle it properly which will affect to the pilgrim journey and service received not as per agents promised is an example of issue occur today (Buang, 2017). According to Kiki & Adrian (2014) increasing to Umrah leads to increasing number of fraud cases on potential pilgrims however the government promises to take down the license of travel agency that proved to swindle Umrah travel agency. There are not yet research regarding this topic, but there are a lot of studies about Travel Agency. The dependent variable in this study is "Factor influencing the selection of umrah travel agency". The independent variables are trust, cost value, attractive marketing and customer services. Thus, the present study has shown that cost value and customer service have a significant relationship with the selection of Umrah travel agency. However, for trust and attractive marketing, there are not having significant relationships with the selection of Umrah travel agency. In a nutshell, cost value is the most factors that contribute to the selection of Umrah travel agency: a case study in Kuala Lumpur and Selangor.